Protective Effect of Vitamin A against Oxidative Stress Caused by Methotrexate - Sail, Asmaa; Al-Mahdawi, Ferial; Al-Lami, Makarim; Al-Jalabi, Salah (Iraqi Journal of Science, 2023)
Methotrexate (MTX), a folate antagonist agent, is mainly used in treatment ofmalignant tumors and autoimmune diseases. The present study was undertaken todetermine whether antioxidant vitamin (vitamin A) could ameliorate methotrexateinducedoxidative stress in male rabbits. Twenty male rabbits were randomlyassigned into four groups. Group 1: control group, Group 2: MTX-treated group(received 20 mg/kg MTX intraperitoneally), Group 3: Vit.A treated group received5000 IU Vit.A orally) and Group 4: MTX+Vit.A treated group received MTX 20mg/kg plus 5000 IU vit.A). After 4 weeks of treatment, blood samples werecollected by cardiac puncture to determine the serum malondialdehyde (MDA), as agood indicator for lipid peroxidation and oxidative stress. The results showed thatthere was a significant increase (p<0.05) in serum MDA level in MTX-treated groupcompared with control group. Also, the results revealed that there was a significantdecrease (p<0.05) in serum MDA level in MTX+Vit.A treated group in comparisonwith MTX-treated group. The present study suggests that the administration of vit.Awith MTX is associated with reduction in oxidative stress, and therapeutic role inreduced toxicity of MTX.